Do Foreign-Owned Firms Provide More Formal Training Than Their Domestic Counterparts? - Zulfiu Alili, Merita (European Journal of Sustainable Development, 2018)
Transition economies compete for FDI since it is expected to have net benefits for the host economy in terms of employment by creating jobs, paying higher wages, offering more training compared to the local firms, as well as benefits for the balance of payments, technology, growth and the alleviation of poverty. This paper examines if foreign-owned firms are more likely to provide formal training to their employees after controlling for other firm characteristics. This empirical analysis uses firm level data from the Business Environment and Enterprise Performance Survey (BEEPS) 2002-2009. To investigate the impact of foreign ownership on the provision of training this paper is using the Probit, Tobit and Craggit models. The empirical evidence presented in this paper indicates that foreign ownership has a positive and significant impact upon the incidence and intensity of training for both non-production and production workers using pooled cross-section data. Keywords: FDI, provision of training, firm level data, Probit, Tobit, Craggit model